Wykonaj redukcję wyrazów podobnych i oblicz wartość liczbową każdgo wyrażenia dla a = - 3 b = -⅓ c=2

a)-3abc + 2a²b² - 3ab - a²b² + 4abc
b) 7ac - 4ab + 8bc - 6ac + 12ab - 10bc
c)-2a²b²c + 2ab²c³ - 3a²b²c² + 4a³b²c

Proszę :)

1

Odpowiedzi

2010-02-10T18:37:31+01:00
-3abc + 2a2 - b2 - 3ab-a2 * b2 + 4abc =
= -3(-3 * - * 2) + 2(-3)2 - b(-)2 - 3(-3*-) - 32 * -2 + 4(-3 * (-) * 2) =
= -18 + (-18) + 9 - 9 + 24 =
= -36 + 24 = -12

7ac - 4ab + 8bc - 6ac + 12ab - 10bc =
= 7(-3*2) - 4(-3 * -) + 8(-2) - 6(-3*2) + 12(-3 * -) - 10(-*2) =
= -42-12-16-36+36-20 =
= -90

-2a2... = -2(-3)2 * (-)2 * 2=
= 36-48-108+216 =
= 96